Drop attacks, falls and atonic seizures in the Video-EEG monitoring unit. (November 2015) - Baraldi, Sara; Farrell, Fiona; Benson, Jennifer; Diehl, Beate; Wehner, Tim; Kovac, Stjepana
Highlights: Drop attacks, falls and atonic seizures are rare in the adult population. These seizure types are associated with learning difficulties. Half of the patients suffering from these seizure types had frontal lobe lesions. Ictal EEG patterns were attenuation, paroxysmal fast and generalised spike wave. Abstract: Purpose: We set out to determine clinical and EEG features of seizures presenting with falls, epileptic drop attacks and atonia in the video EEG monitoring unit. Methods: We searched the video EEG monitoring reports over a 5-year-period for the terms "drop", "fall" and "atonic". Results: Seizures presenting as epileptic drop attacks, falls or atonia were found in 23/1112 (2%) admissions. About half of the patients suffering from these seizure types had developmental delay and learning difficulties and in half of the patients a lesion was seen on MRI which was often frontal. The presumed epileptogenic zone was frontal in many cases (43%), unclear with regards to a region or multifocal in 48% and posterior temporal/occipital in 2 patients (9%). EEG patterns recorded were paroxysmal fast activity, spike and wave discharges and EEG attenuation. Seizure related falls were seen in 8 cases (34%) with injuries recorded during Video EEG monitoring in half of those. Conclusion: Clinical and EEG features outlined here can help the clinician to recognise patients at risk for these devastating seizure types.